2015
DOI: 10.1002/macp.201500354
|View full text |Cite
|
Sign up to set email alerts
|

Selective Chain Alignment of Conducting Polymer Blend Films by an Ultrafast Laser

Abstract: Tunable and selective areal polymer chain alignment method is developed for spin-cast blend fi lms of poly(3-hexylthiophene)(P3HT):[6,6]-phenyl-C61-butlyric methyl ester (PCBM) system by a femtosecond laser process. The chain alignment, phase separation, and molecular structure of the laser exposed P3HT:PCBM fi lms are investigated by grazing incidence wide angle X-ray scattering and micro-Raman analysis. The alkyl chains of P3HT polymer become highly ordered along the polarization axis of the laser. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…1). Considering the enhanced properties of PEDOT:PSS hydrogels attributed to the phase separation of PEDOT:PSS through dry annealing processes ( 13 , 14 ) and strong electric field ( 15 17 ) reported in previous studies, we hypothesized that a laser can give both photothermal energy and electric field to PEDOT:PSS simultaneously ( 22 ). The photothermal energy would locally make the PEDOT and PSS two-phase system unstable, and then the strong electric field was able to separate the PEDOT and PSS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Considering the enhanced properties of PEDOT:PSS hydrogels attributed to the phase separation of PEDOT:PSS through dry annealing processes ( 13 , 14 ) and strong electric field ( 15 17 ) reported in previous studies, we hypothesized that a laser can give both photothermal energy and electric field to PEDOT:PSS simultaneously ( 22 ). The photothermal energy would locally make the PEDOT and PSS two-phase system unstable, and then the strong electric field was able to separate the PEDOT and PSS.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we developed a novel biocompatible and ultrafast digital patterning process to fabricate water-stable PEDOT:PSS hydrogels via the laser-induced phase separation of PEDOT:PSS (LIPSP). We took advantage of the unique characteristics of a continuous-wave laser ( 22 ), which can provide a strong electric field and photothermal energy in an ultrafast time scale to induce the phase separation of PEDOT:PSS. To intensify the interaction between PEDOT:PSS and the laser, plasmonic gold nanoparticles (AuNPs) ( 23 ) were added, and the degree of phase separation according to the AuNP concentration was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Recently, it has been reported that a single pulse femtosecond laser irradiation could induce alkyl chain alignment along a polarization direction of the laser in a poly(3-hexylthiophene) (P3HT): [6,6]-phenyl-C 61 -butyric methyl ester (PC 61 BM) blend film, which is an archetypal system in conjugated polymers for OSCs. 22 The chain alignment in a certain direction could be advantageous to increase electrical properties in conjugated polymer systems. However, the effects of the femtosecond laser irradiation on the electrical properties of the film have not been entirely undiscovered.…”
mentioning
confidence: 99%
“…In addition, a compatible technology for OSC has been described with optimal formation of laser-induced periodic surface structures (LIPSS). Ripples created by LIPSS with multiple laser pulses in P3HT and PCBM have been successfully formed and shown the possibility into organic photovoltiacs. , Recently, it has been reported that a single pulse femtosecond laser irradiation could induce alkyl chain alignment along a polarization direction of the laser in a poly­(3-hexylthiophene) (P3HT): [6,6]-phenyl-C 61 -butyric methyl ester (PC 61 BM) blend film, which is an archetypal system in conjugated polymers for OSCs . The chain alignment in a certain direction could be advantageous to increase electrical properties in conjugated polymer systems.…”
mentioning
confidence: 99%